The Level of Effectiveness Use of Quinoline Drugs in COVID-19: A Literature Review - M.Dedi Dermawan Dermawan; Afrita Amalia Laitupa; Muslim Andala Putra; Nenny Triastuti (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACT          Chloroquine is the first line of medicine in the treatment of malaria. Besides being antimalaria, the chloroquine also can be used as the anti-inflammation in the medicine of arthritis rheumatoid arthritis and lupus erythematosus discoid. Hydroxychloroquine sulfate is 4-aminoquinolin with hydroxylated chloroquine analog, having the same pharmacokinetic as chloroquine which is given orally in hydroxychloroquine sulfate form, processed by gastrointestinal absorption and very faster kidney elimination. The effectiveness of chloroquine and hydroxychloroquine towards COVID-19 in the in vitro experiment showed it could inhibit the duplication of the SARS-CoV-2 virus. The chloroquine function is to stop COVID-19 infection with (EC50) 1,13 μM and (CC50) larger than 100 μM. Meanwhile, the hydroxychloroquine function is to inhibit the attachment and entry of the virus into the host’s cell by enzymatic activation which is the lysosome acidification disorder and antigen presentation as the result of pH increase. Based on the clinical study, the 10 of 12 patients who have lopinavir/ritonavir therapy by virology, the chloroquine group showed RT-PCR negative on day 7, 10, and 14 in compare to lopinavir/ritonavir that showed RT-PCR negative on day 14. On the 9th day, 60% of the patients of chloroquine group showed the CT scan of Lungs image normal instead of the lopinavir/ritonavir at 25%. In the day 14 based on the CT test result, the pulmonary improvement increased twice rather than chloroquine group (Rate Ratio 2.21). It proved that the chloroquine role showed the result of the medicine has a significant effect by cleaning the virus or other clinical matters. The purpose of this literature review is to know the effectiveness quinoline class of drugs which is chloroquine and hydroxychloroquine in COVID-19 disease.Keywords: effectiveness, chloroquine, COVID-19Correspondence: dedydermawan555@gmail.com